An Evaluation Study on Growth Centre Scheme in Akola Dist. Maharashtra Part A - Planning Commission (Planning Commission, 2002)
To boost the economic growth and maintain the regional balance the Central Govt, had introduced the scheme “Growth Centre"" to establish industries in backward districts of country in the year 1988. Conceptually these Growth Centres were to be located on a land of 400-800 hectors area in backward but suitable districts where all necessary infrastructures can be developed by Central and State Govt, jointly. The entrepreneurs can start their enterprise in these centres to support to increase industrial production. These centres are expected to help promotion of small and medium scale unit. On the basis of studies made by various State Govt, experts, the committee of Central Govt, identified 68 Centre in 25 States of country and approved in March 1992. The Central Govt, extended financial assistance to the extent of Rs. 1000.00 Lakhs to each centre as equity and rest of cost of about Rs. 20 Lakhs, to Rs. 25 Lakhs is to be contributed by State Govts.
Prepared For : Government Of India, Planning Commission, Yojana Bhavan, New Delhi - 110 001 Prepared By : Mitcon Consultancy Services Limited Kubera Chambers, Shivajinagar, Pune-411 005